Concert of the Vienna Philharmonic, February 27, 1940 - Wiener Philharmoniker::::::::::::::: (Germany; Berlin, 2020)
Program of a concert by the Vienna Philharmonic, conducted by Hans Knappertsbusch, in Berlin on February 27, 1940, sponsored by the National Socialist German Workers (NAZI) Party. The concert included a performance of Beethoven's Fifth Symphony, op. 67.